Menilik Problematika Dispensasi Nikah Dalam Upaya Pencegahan Pernikahan Anak Pasca Revisi UU Perkawinan - Ahmad Muqaffi; Rusdiyah Rusdiyah; Diana Rahmi (JOURNAL OF ISLAMIC AND LAW STUDIES, 2021)
Abstract: Highlighting the potential discrepancy between the Child Protection Law (No. 35/2014) and the Marriage Law (No. 16/2019) in the issue of marrying children under the minimum age of marriage, which is 19 years. Parents are obliged to "prevent child marriage" according to Article 26 paragraph 1 letter c of the Child Protection Law (No. 35/2014), but Article 7 Paragraph 2 of the Marriage Law (No. 16/2019) actually opens up opportunities for parents to marry off. the child is still not old enough without violating state regulations. As a normative legal research with a statute approach, juxtaposing the two seemingly out of synchrony of the two laws in question and analyzing the law. In addition, it also describes the problems of child marriage so that it is prohibited by the state.Â Abstrak: Menyoroti potensi ketidaksinkronan antara Undang-Undang Perlindungan Anak (No. 35/2014) dan Undang-Undang Perkawinan (No. 16/2019) dalam isu menikahkan anak di bawah usia minimal kawin, yakni 19 tahun. Orang tua wajib â€œmencegah terjadinya perkawinan pada usia anakâ€ menurut Pasal 26 ayat 1 huruf c UU Perlindungan Anak (No. 35/2014), namun Pasal 7 Ayat 2 UU Perkawinan (No. 16/2019) justru membuka peluang orang tua dapat menikahkan anaknya yang masih belum cukup umur tanpa melanggar aturan negara. Sebagai penelitian hukum secara normatif dengan pendekatan perundang-undanganÂ (statute approach), menyandingkan kedua pasal yang tampak tidak sinkron dari dua UU dimaksud dan menganalisis implikasi hukumnya. Selain itu juga menjabarkan problematika pernikahan anak di bawah umur sehingga dilarang oleh negara.